LANGUAGE AWARENESS IN GEOGRAPHY EDUCATION: AN ANALYSIS OF THE POTENTIAL OF BILINGUAL GEOGRAPHY EDUCATION FOR TEACHING GEOGRAPHY TO LANGUAGE LEARNERS - Michael Morawsk; Alexandra Budke (European Journal of Geography, 2017)
The current migration and refugee flows and increasing linguistic heterogeneity in German social science classes have changed teaching. It is a change towards language-aware teaching. The article assesses the question of how bilingual geography teachers’ language perception could help to develop language-aware geography education. The hypothesis is that bilingual teachers, due to the simultaneous teaching of content and language, develop and use detailed language awareness in geography. A model of the language in geography classrooms, which defines requirements of language actions there, is presented. 16 bilingual geography teachers in secondary schools in Germany were interviewed over six months to assess their language awareness by a qualitative analysis referring to the model. The results show that bilingual geography teachers assume key values related to language-awareness in geographic language. These results strongly allow discussion of language-aware implications, particularly in terms of structuring, visualization and transparency of discourse functions.